Celery-like nitrogen and phosphorous co-doped carbon nanofiber frameworks supporting oxygen reduction and methanol oxidation electrocatalysis. (19th March 2023) - Huang, Guo; Ali, Asad; He, Shaobo; Luo, Shuiping; Shen, Pei Kang; Zhu, Jinliang
Abstract: Doped materials with well-defined morphologies have attracted substantial research interest due to their excellent activity and stability in fuel cells. Herein, celery-like nitrogen and phosphorous co-doped carbon nanofibers frameworks (PNCNF) have been successfully fabricated via a novel in-situ doping and self-assembly strategy, serving as superior supports for uniform Pt nanoparticles. The resulting Pt/PNCNF composite possesses a porous architecture and high-surface area, which exhibits remarkable mass activity, durability, and anti-poisoning ability towards oxygen reduction and methanol oxidation reactions, compared to the commercial Pt/C electrocatalyst. In addition, the high CO tolerance of Pt/PNCNF could be ascribed to a strong interaction between the Pt nanocrystals and PNCNF, which facilitates OH − adsorption to remove CO intermediate. The improved electrocatalytic properties benefit from the morphological and compositional advantages of the N and P co-doped carbon nanofiber frameworks. Specifically, the orientation of celery-like carbon nanofibers layers in Pt/PNCNF optimizes its mechanical properties. This synthetic strategy for the preparation of N and P co-doped carbon is envisaged as a new and general pathway for the rational engineering of heteroatom doped carbon composites for renewable energy conversion applications. Graphical abstract: Image 1 Highlights: A novel celery-like nitrogen and phosphorous co-doped carbon nanofibers frameworks (PNCNF) have been fabricated. Pt/PNCNF facilitates 3 times mass activity of that on commercial Pt/C for ORR. DFT results indicates Pt/PNCNF possesses superior O2 adsorption energy compared with Pt/C. Pt/PNCNF exhibits a much lower onset potential and higher peak mass activity compared with Pt/C.